Seed Dressing Containing Gibberellic Acid, Indole-3-Acetic Acid, and Brassinolide Improves Maize Seed Germination and Seedling Growth Under Cold Stress - Jingjing Cui; Liqiang Zhang; Qianqian Li; Yuan Qi; Jiajun Ma; Danyang Guo; Pengyu Zhang; Yujie Xu; Yan Gu; Hongyu Wang (Agronomy)
Chemical products, such as seed dressings, are often used to regulate crop growth and development and improve yields. In this study, we investigated a seed dressing containing 0.136% gibberellic acid (GA), indole-3-acetic acid (IAA)-, and brassinolide (BL) as a wettable powder (WP), hereafter referred to as GA-IAA-BL WP. This product is a new plant growth regulator of plant origin that can improve crop stress resistance and yield. However, its effect on maize seed germination and seedling growth under low-temperature stress is unclear. In this study, GA-IAA-BL WP was applied to maize ‘Liukexing 99’ seeds at 50, 100, 150, or 200 mg mL−1, and seeds were germinated in an artificial climatic chamber at 10, 15, or 25 °C for 14 d. Application at 100 mg mL−1 significantly increased the germination rate as well as seedling shoot and root length and dry and fresh weight at all three temperatures. This application rate also increased the contents of proline, malondialdehyde, soluble sugars, and soluble proteins; the activities of catalase, superoxide dismutase, and peroxidase; and root vigor. Our results demonstrate that GA-IAA-BL WP can reduce the negative impacts of low-temperature stress on seed germination and seedling growth.